A Gong Angin: Organological and Musical Innovation in Creating Music Based on Flute Instruments - Fredy, Catur; Sukerta , Pande Made (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
The flute is a great source of inspiration in creating new musical instruments. The creation of the Gamelan Flute artwork was carried out to explore the source of ideas for flute instruments, which will then be realized in the form of creating a new set of musical instruments, developments from modified flute instruments with the aim of looking for updates to other forms, both in terms of visual form, technique and function. For this reason, there is a need for organological and musical innovation in the creation of music based on flute instruments. When trying to develop a new musical instrument, creators can take elements of the flute that they find interesting and combine them with creative ideas. By developing flute instruments or using modern technology in making instruments, artists can create unique and interesting sounds, providing a deeper artistic dimension and expressing themselves in new ways in their work. Understanding this cultural background and integrating it into the design of a new musical instrument can hopefully produce something unique and valuable.